Characterization of the epidemiological profile of Visceral Leishmaniasis in the municipality of Parnaíba-PI, from 2009 to 2019 (Research, Society and Development, 2023)
This study aimed to analyze and characterize the epidemiological profile of cases of Visceral Leishmaniasis (VL) in the city of Parnaiba-pi, in the years 2009 to 2019. This is a quantitative and descriptive study. The survey was conducted using the data available in the National System of Notifications and Diseases (Sinan), with an analysis of the variables: number of cases of VL per year, gender, education, age and area of residence. Thus, a total of 107 cases were reported. There was an upward trend in the number of cases since 2011. This trend can be justified by the adoption of disease prevention measures in recent years. Analyzing the patients' gender, 72 were male and 35 were female. In the age group, the highest number of cases occurred in people between 20 and 39 years. Regarding education, 14 people had from 1st to 4th grade and only 7 had high school. As for the area of residence, 75 affected lived in the urban area and 30 in the rural area. Thus, although VL presents an increasing trend in the number of cases, the number of individuals affected by this pathology is still significant. This finding reaffirms the need for a more expressive approach by the public health sectors.